Design and synthesis of bile acid-based amino sterols as antimicrobial agents - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Shukla, Praveen K.; Gonnade, Rajesh G. (Bioorganic & Medicinal Chemistry Letters, 2009)
New bile acid-based amino sterols were synthesized in good yields from C-3 beta-oxiranes as key intermediates. These derivatives were evaluated for their in vitro antimicrobial properties against human pathogens. These compounds showed better antibacterial activity as compared to antifungal activity. Compounds 21 and 22 showed comparable antibacterial activity to gentamicin against Staphylococcus aureus with IC(50) values of 5.14 and 4.46 mu g/mL. This is the first report for the synthesis of C-3 beta-oxiranes on the steroids having A/B cis ring junction and these oxiranes have been used for the synthesis of amino sterols 17, 18, 21, and 22. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amino sterols; Antibacterial agent; bile acid; Oxirane